4f → 3d sensitization: a luminescent EuII–MnII heteronuclear complex with a near-unity quantum yield. Issue 2 (14th December 2022) - Yu, Gang; Liu, Huanyu; Yan, Wenchao; Guo, Ruoyao; Wu, Aoben; Zhao, Zifeng; Liu, Zhiwei; Bian, Zuqiang
Abstract : A new heteronuclear Eu II –Mn II complex with high photoluminescence quantum yield is designed and synthesized, which represents the first example of f → d molecular sensitization. Abstract : A new heteronuclear Eu II –Mn II complex [Eu(N2O6)]MnBr4 (N2O6 = 4, 7, 13, 16, 21, 24-hexaoxa-1, 10-diazabicyclo[8.8.8]hexacosane) is designed and synthesized, which shows an intense green emission from Mn II with a near-unity photoluminescence quantum yield. Measurement of excited-state dynamics demonstrated the sensitization process from Eu II to Mn II, which represents the first example of f → d molecular sensitization. Due to the large optical absorption cross-section of the Eu II center, [Eu(N2O6)]MnBr4 shows an emission intensity 7 to 2500 times stronger than that of the Sr II –Mn II control complex [Sr(N2O6)]MnBr4 upon the excitation of near ultraviolet to blue light.